Warburg’s Ghost—Cancer’s Self-Sustaining Phenotype: The Aberrant Carbon Flux in Cholesterol-Enriched Tumor Mitochondria via Deregulated Cholesterogenesis - Coleman, Peter S.; Parlo, Risa A. (Frontiers in Cell and Developmental Biology, 2021)
Interpreting connections between the multiple networks of cell metabolism is indispensable for understanding how cells maintain homeostasis or transform into the decontrolled proliferation phenotype of cancer. Situated at a critical metabolic intersection, citrate, derived via glycolysis, serves as either a combustible fuel for aerobic mitochondrial bioenergetics or as a continuously replenished cytosolic carbon source for lipid biosynthesis, an essentially anaerobic process. Therein lies the paradox: under what conditions do cells control the metabolic route by which they process citrate? The Warburg effect exposes essentially the same dilemma — why do cancer cells, despite an abundance of oxygen needed for energy-generating mitochondrial respiration with citrate as fuel, avoid catabolizing mitochondrial citrate and instead rely upon accelerated glycolysis to support their energy requirements? This review details the genesis and consequences of the metabolic paradigm of a “truncated” Krebs/TCA cycle. Abundant data are presented for substrate utilization and membrane cholesterol enrichment in tumors that are consistent with criteria of the Warburg effect. From healthy cellular homeostasis to the uncontrolled proliferation of tumors, metabolic alterations center upon the loss of regulation of the cholesterol biosynthetic pathway. Deregulated tumor cholesterogenesis at the HMGR locus, generating enhanced carbon flux through the cholesterol synthesis pathway, is an absolute prerequisite for DNA synthesis and cell division. Therefore, expedited citrate efflux from cholesterol-enriched tumor mitochondria via the CTP/SLC25A1 citrate transporter is fundamental for sustaining the constant demand for cytosolic citrate that fuels the elevated flow of carbons from acetyl-CoA through the deregulated pathway of cholesterol biosynthesis.